Pemanfaatan teknologi pakan ikan otomatis untuk ketahanan pangan di Kelurahan Ciamis Kabupaten Ciamis - Zulfi Miftahudin Zulfi; Setio Galih Marlyono; Prama Permana; Mohammad Syarif AL Huseiny (IKIP SILIWANGI, 2024)
The impact of Covid-19 is felt in society. Many of the limited community carry out activities to meet their economic needs. Let alone many activities at one time, one activity in a public location which is strictly limited by government policy. This was complained by fish farmers in Ciamis Village, Ciamis Regency who are members of the Sumur Kupa farmer group who have limited time to provide fish feed to their respective ponds. Based on these problems, an alternative solution was created, namely utilizing technology to provide fish feed automatically without having to regularly come to the pond. The use of this technology is accompanied by a series of trainings for use by the community. The main method used in training is demonstration, simulation, and practice of installing automatic fish feed equipment using solar panels. The partners we collaborated with in this PbM-KP activity were: 1) Ciamis Village as a related agency so that they were able to re-socialize to the wider community, and 2) Residents of RW 28 Rancapetir who were members of the Sumur Kupa farmer group in Ciamis Village as a community group that was used as a community group. pilot for the implementation of automatic fish feeding technology. Keywords: Impact of Covid-19, Technology, Automatic Fish Feeding Equipment